Clinical Outcomes Associated With Methylprednisolone in Mechanically Ventilated Patients With COVID-19. (9th August 2020) - Nelson, Brian C; Laracy, Justin; Shoucri, Sherif; Dietz, Donald; Zucker, Jason; Patel, Nina; Sobieszczyk, Magdalena E; Kubin, Christine J; Gomez-Simmonds, Angela
Abstract: Background: The efficacy and safety of methylprednisolone in mechanically ventilated patients with acute respiratory distress syndrome resulting from coronavirus disease 2019 (COVID-19) are unclear. In this study, we evaluated the association between use of methylprednisolone and key clinical outcomes. Methods: Clinical outcomes associated with the use of methylprednisolone were assessed in an unmatched, case-control study; a subset of patients also underwent propensity-score matching. Patients were admitted between 1 March and 12 April, 2020. The primary outcome was ventilator-free days by 28 days after admission. Secondary outcomes included extubation, mortality, discharge, positive cultures, and hyperglycemia. Results: A total of 117 patients met inclusion criteria. Propensity matching yielded a cohort of 42 well-matched pairs. Groups were similar except for hydroxychloroquine and azithromycin use, which were more common in patients who did not receive methylprednisolone. Mean ventilator-free days were significantly higher in patients treated with methylprednisolone (6.21 ± 7.45 vs 3.14 ± 6.22; P = .044). The probability of extubation was also increased in patients receiving methylprednisolone (45% vs 21%; P = .021), and there were no significant differences in mortality (19% vs 36%; P = .087). In a multivariable linear regression analysis, only methylprednisolone use was associated with a higher number of ventilator-free days ( P = .045). The incidence of positive cultures and hyperglycemia were similar between groups. Conclusions: Methylprednisolone was associated with increased ventilator-free days and higher probability of extubation in a propensity-score matched cohort. Randomized, controlled studies are needed to further define methylprednisolone use in patients with COVID-19. Abstract : In a propensity-matched cohort study, ventilator-free days and the probability of extubation were both significantly increased in patients receiving methylprednisolone at 28-day follow-up. The incidence of hyperglycemia and positive cultures were not increased.